Collaboration of Academic Advisor with Counseling Laboratories and its effect on the Students’ Learning Readiness - Dina Hajja Ristianti; Beni Azwar; Irwan Fathurrochman; Nurjannah Nurjannah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The academic advisor and college counselling laboratories have an essential role in giving services to students. One of the assumptions is that these services can impact student learning readiness. This study aims to see how the relationship between Academic Advisors and the counselling labour impairs students' preparedness for learning. This research is quantitative research with a sample size of 297 people from seventeen studies programs for the 2019/2020 school year, where the sample is taken at random (random sampling). Instrument to measure the synergy and readiness to learn using a closed questionnaire Likert scale model. The data validation and data reliability are carried out through statistical analysis apps in the 21st version. The results showed that the correlation coefficient obtained between the variables of Academic Advisory and counselling laboratories and the variable of student learning readiness was 0.851, which was included in the fairly high or strong category. So it can be concluded that there is a synergy between Academic Advisors and counselling laboratories in providing services to students and also impacts student learning readiness.